THE IMPORTANCE OF THE MULTI-PARTY SYSTEM IN THE DEVELOPMENT OF DEMOCRACY (Academicia Globe: Inderscience Research, 2023)
One of the most researched and urgent problems of political science in world science is precisely the issues related to political parties. The problems of the political party and the party system are being changed and renewed as a result of globalization and the development of modern information and communication technologies. This article aims to reveal the importance of the multi-party system in the development of democracy, which is the most studied of the party systems. Comparative analysis with other party systems is also done.